The emerging role of long non-coding RNAs in schizophrenia - Wu, Guangxian; Du, Xinzhe; Li, Zexuan; Du, Yanhong; Lv, Jinzhi; Li, Xinrong; Xu, Yong; Liu, Sha (Frontiers in Psychiatry, 2022)
Schizophrenia (SZ) is a severe psychiatric disorder which is contributed by both genetic and environmental factors. However, at present, its specific pathogenesis is still not very clear, and there is a lack of objective and reliable biomarkers. Accumulating evidence indicates that long noncoding RNAs (lncRNAs) are involved in the pathophysiology of several psychiatric disorders, including SZ, and hold promise as potential biomarkers and therapeutic targets for psychiatric disorders. In this review, we summarize and discuss the role of lncRNAs in the pathogenesis of SZ and their potential value as biomarkers and therapeutic targets.